2013
DOI: 10.4049/jimmunol.1300490
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Derived IL-33 Is a Critical Factor for Placental Growth

Abstract: IL-33, the most recently discovered member of the IL-1 superfamily and ligand for the transmembrane form of ST2 (ST2L), has been linked to several human pathologies including rheumatoid arthritis, asthma, and cardiovascular disease. Deregulated levels of soluble ST2, the natural IL-33 inhibitor, have been reported in sera of preeclamptic patients. However, the role of IL-33 during healthy pregnancy remains elusive. In the current study, IL-33 was detected in the culture supernatants of human placental and deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 62 publications
7
60
0
Order By: Relevance
“…22 To confirm these findings, we re-examined ADAM12 localization in early (5-7 weeks gestation) and late (10-12 weeks gestation) first trimester placentae by immunofluorescence microscopy; the trophoblast markers hepatocyte growth factor activator inhibitor-1 (HAI-1), HLA-G and KRT7, as well as the proliferation marker Ki67 helped identify distinct trophoblast populations. 26 ADAM12 localized strongly to HLA-G + EVT columns and apically in the synCT (Figure 1a). ADAM12 positivity was also noted in trophoblasts localized proximal to Ki67 + EVTs and stochastically to HAI-1 + vCTs; ADAM12 preferentially localized to proliferative areas within floating villi noted by strong Ki67 positivity in serial sections ( Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…22 To confirm these findings, we re-examined ADAM12 localization in early (5-7 weeks gestation) and late (10-12 weeks gestation) first trimester placentae by immunofluorescence microscopy; the trophoblast markers hepatocyte growth factor activator inhibitor-1 (HAI-1), HLA-G and KRT7, as well as the proliferation marker Ki67 helped identify distinct trophoblast populations. 26 ADAM12 localized strongly to HLA-G + EVT columns and apically in the synCT (Figure 1a). ADAM12 positivity was also noted in trophoblasts localized proximal to Ki67 + EVTs and stochastically to HAI-1 + vCTs; ADAM12 preferentially localized to proliferative areas within floating villi noted by strong Ki67 positivity in serial sections ( Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…For example, a number of decidual growth factors secreted starting at implantation likely support trophoblast invasion. Similarly, the maternal immune system is not simply suppressed at the introduction of the allograft but rather modulated to add active support (Knofler and Pollheimer 2012;Erlebacher 2013;Fock et al 2013). Given the pervasive evidence for mutual interaction between maternal and fetal tissues, the resulting utero-placental phenotype is best conceptualized as a unit resulting from a rich network of developmental interactions.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…Newborns demonstrate enhanced Th2 cell function, which is believed to be the result of a complex feto-maternal symbiosis. Th2 cell immunity suppresses alloresponses during pregnancy and promotes growth of the placenta (Fock et al, 2013;Forsthuber et al, 1996). The enhanced Th2 cell bias of neonatal T cells is in part T cell intrinsic and transient (Li et al, 2004;Sornasse et al, 1996;White et al, 2002), but cord blood DCs have also been shown to lack production of the Th1-cell-polarizing cytokine IL-12p70 (Goriely et al, 2001;Upham et al, 2002).…”
Section: Introductionmentioning
confidence: 99%